Case Report: Effectiveness Of Aloe Vera Compress And Breast Care In Reducing Breast Pain And Engorgement Among Postpartum Mothers - Tri Lestari Handayani; Dewi Oktaviani; Lisnadiyanti (CV Media Inti Teknologi, 2026)
Background of study: Breast pain and breast engorgement are common problems experienced by postpartum mothers, especially during the early days after childbirth. These conditions may interfere with breastfeeding and reduce maternal comfort. Aims and scope of paper: This study aimed to analyze the effectiveness of aloe vera compress combined with breast care in reducing breast pain and breast engorgement in postpartum mothers. Methods: This study used a case report design involving three postpartum mothers who experienced breast pain and breast engorgement. Participants received aloe vera compress therapy for 30 minutes followed by breast care procedures for 20 minutes, twice daily for three consecutive days. Pain was measured using the Numeric Rating Scale (NRS), while breast engorgement was assessed using the Six Point Engorgement Scale (SPES). Result: The results showed a reduction of 2,66 points in pain scores (NRS) and a decrease of 3,32 points in breast engorgement scores (SPES) after the intervention. Conclusion: The combination of aloe vera compress and breast care was effective in reducing breast pain and breast engorgement in postpartum mothers and may be considered a complementary non-pharmacological nursing intervention